Production of anti-rM14 and anti-rM42 antibodies and their application in the study of expression of metalloproteases M14 and M42 of keratinolytic strain of Bacillus paralicheniformis - Maduakhassova , A.; Mussakhmetov , A.; Akishev , Zh.; Aktayeva, S.; Khassenov , B. (Eurasian Journal of Applied Biotechnology, 2024)
In the present study, two metalloproteases M14 and M42 from a Kazakh strain of Bacillus paralicheniformis T7 with high proteolytic activity were successfully cloned, expressed and purified. Protease genes were amplified by polymerase chain reaction (PCR) using specific primers selected on the basis of full genome sequencing data of B. paralicheniformis strain N7 (GenBank accession #CP124861). The amplified fragments were cloned in the expression vector pET-28c(+). Recombinant analogs of the metalloproteases M14 and M42 were obtained by plasmid expression in Escherichia coli cells of the strain ArcticExpressRP(DE3). Using metal affinity chromatography, rM14 and rM42 proteins were purified and polyclonal antibodies were produced by immunization of rabbits. Using anti-rM14 and anti-rM42 antibodies, the expression level of native metalloproteases M14 and M42 in cell lysate and culture fluid of B. paralicheniformis T7 strain was examined after culturing the strain on keratin-containing media: chicken feather, horn, hoof, hide and wool of cattle. Substrate-dependent expression of metalloprotease genes of B. paralicheniformis strain T7 was established. The obtained results indicate the prospective use B. paralicheniformis strain T7 as a producer of metalloproteases M14 and M42.